Central auditory system assessment in children and adolescents with cystic fibrosis: electrophysiology and central auditory processing - Paula Maria Martins-Duarte; Gabriel Hessel; Antônio Fernando Ribeiro; Fernando Augusto Lima Marson; Maria Francisca Colella-Santos (Jornal de Pediatria)
Objective: This study aims to evaluate the central auditory system of children and adolescents with cystic fibrosis through behavioral assessment of central auditory processing and electrophysiological tests to investigate short and long-latency auditory potentials, comparing them with the results obtained in the control group. Methods: 117 from 7 to 21 years old patients were evaluated, 57 of them with cystic fibrosis and 60 of the control group, using behavioral evaluation of central auditory processing, auditory brainstem response and long latency auditory evoked potential. The comparison of the research groups was performed using ANOVA for Auditory Brain Response and P300 responses and Wilcoxon and Mann-Whitney tests for Central Auditory Processing responses. Results: A statistically significant difference was found in the results of the GIN test between the groups and in the auditory brainstem response latency responses in waves I and V in the comparison between the groups with higher latencies in the study group. A difference was also found between latencies in the interpeak intervals I-III and III-V. The long latency auditory evoked potential analysis shows a statistically significant difference in the latency of the P300 potential, with higher latencies in the study group. Conclusion: Cystic fibrosis participants presented worse performance in the gaps-in-noise test compared to the control group in the evaluation of central auditory processing, which indicates impairment of temporal resolution auditory ability. They also showed increased latency in I and V waves of auditory brainstem response, as well as an increase P300 latency in long latency auditory evoked potential.